Autumn and spring migration of the Taiga Bean Goose Anser fabalis middendorffii in northern Japan from 2002 to 2012, with implications for site conservation - Ikawa, Hiroshi; Ikawa, Marie-Jo (Wildfowl, 2013)
The Taiga Bean Goose Anser fabalis middendorffii is classified as â€œnear threatenedâ€ (NT) on Japanâ€™s Red List with c. 9,000 birds wintering in the country. The Sarobetsu Plain, northern Hokkaido, is an important staging area for the geese migrating between northeast Russia and Honshu, Japan. Over the period 2002â€“2011, peak numbers staging at Sarobetsu each autumn ranged from 6,178â€“9,230 birds (mean Â± s.e. = 7,272 Â± 267), suggesting that most Taiga Bean Geese wintering in Japan migrate through Sarobetsu. The duration of autumn staging ranged from 51â€“87 days (mean = 74 Â± 3) across the years. Lakes Kabuto and Penke and the Teshio Oxbow Lakes were the main autumn roost sites. In spring, peak numbers at the site varied from 1,486â€“2,776 individuals (mean = 2,048 Â± 140; 2002â€“2012), and the geese were present for 23â€“50 days (mean = 35 Â± 2). Peak numbers were significantly greater and staging periods were always longer in autumn than in spring. The main spring roost sites were the Furaoi Oxbow Lake and Lakes Penke and Kabuto, confirming the latter two sites as the most important roosts in both autumn and in spring, whereas Furaoi Oxbow Lake was used only in spring. Farmland surrounding these roosts is also important to the birds, as the geese feed mostly in fields close to the roost sites. Two core roosts, Lake Penke and the Furaoi Oxbow Lake, are suffering siltation and adverse effects of fishery activities, which could adversely affect Taiga Bean Geese wintering in Japan.